CLOUD BASED SOFTWARE FOR BIG DATA ANALYTICS IN SMART GRID - MRS.A.B.VALSANG; PRATIKSHA KAKADE; VRUSHALI SURWASE (International Journal of Innovations in Engineering Research and Technology, 2021)
This “Cloud Based software for big data analytics in smart grid” project was challenging to us when we decided to implement this project. Software for the Smart Grid cyber-physical system using cloud technologies. Dynamic Demand Response is a challenge-application to perform intelligent demand-side management and relieve peak load in Smart Power Grids. The platform offers an adaptive information integration pipeline for ingesting dynamic data. In this project we are using HTML, PHP and Mongo DB for developing our software.